(untitled) (Al-Farooq Journal of Sciences, 2026)
The need for more sustainable communities has developed locally, nationally, and globally in this era of limited resources that are contending with increasing population expansion and economic development. Education has long been seen as a path for integrating and advancing sustainable development goals at all stages of the educational system by reorienting the curriculum toward sustainability. In this process, higher education institutes assume a leadership role. However, integrating sustainability into curricula and enhancing students’ competences in sustainability are two of the biggest challenges facing Libyan higher education institutions where students need to be prepared to face the difficulties of creating a more sustainable society with the support of Education for Sustainability (ES). But before achieving this aim, instructors may consider adoptive frameworks of green pedagogy to integrate ES into their curricula. This paper discusses the importance of incorporating sustainability into university courses, how to integrate it, and the difficulties that instructors might face. It is concluded that the integration of sustainability into educational approaches is considered a crucial issue in Libyan higher education. Giving students the knowledge, understanding, and skills that they need to succeed as well as cultivating the next wave of innovators and leaders can potentially bring the change that is required and have a significant impact on the transition to a sustainable future.